Temporal and Spatial Variations of Monsoonal Upwelling along the South West and East Coasts of India. Issue 4 (3rd July 2020) - Patel, Shailee; Vithalpura, Manisha; Mallick, Subrat Kumar; Ratheesh, Smitha
Abstract: The implicit/explicit impact of global warming or the anthropogenic climate change on the coastal upwelling processes affects the marine ecosystem significantly and continuous monitoring of the coastal upwelling along the coastal regions is essential. The Ekman transport due to alongshore winds and Ekman pumping due to wind stress curl play important roles on the coastal upwelling, especially along the southern part of Indian peninsula. Upwelling Indexes based on wind and SST are computed in the study to demarcate the upwelling features along the coasts. Since upwelling leaves its trail on surface features, long time series of satellite-derived wind, Sea Surface Temperature (SST), Sea level anomaly (SLA) and Surface Chlorophyll-a concentration (Chl-a) are analyzed to understand the upwelling along the coastal regions of south India. The present study reveals a decrease in the intensity of upwelling along the western coast (Chl-a ∼ 0.2 mg/m 3 dec −1, Upwelling Index based on wind ( UI wind ) and Vertical Velocity of Ekman Pumping ( VVEP) is approximately 0.0012 m 2 /s dec −1 and 0.120 cm/day dec −1 respectively) and a slight increase all along the eastern coast of southern India during summer monsoon (Chl-a along 11.3°N and 13.9°N is 1 mg/m 3 dec −1, U I wind and VVEP along 10.5°N is 0.0023 m 2 /s dec −1 and 0.2 cm/day dec −1 respectively).